2009
DOI: 10.1002/pon.1539
|View full text |Cite
|
Sign up to set email alerts
|

Actigraphic assessment of daily sleep–activity pattern abnormalities reflects self‐assessed depression and anxiety in outpatients with advanced non‐small cell lung cancer

Abstract: Lung cancer patients whose diurnal activity is disturbed by prolonged and frequent sedentary episodes and whose sleep is disturbed by frequent and prolonged waking are most anxious and depressed. These findings and relationships are masked by hospitalization. Since diurnal exercise improves both sleep and mood, it is reasonable to test whether enhancing daytime activity and nighttime sleep can diminish cancer-associated depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 37 publications
5
53
0
Order By: Relevance
“…Increased comorbidity in our low-RA group is consistent with reduced amplitude of the circadian rest-activity cycle reported in other disease conditions, such as hypertension, 4 cancer, 1 and mood disorders, 46 all conditions taken into account by the COTE index. In their study of schizophrenia patients, Bromundt et al 19 found that low amplitude could be associated with disturbances of circadian rhythms, as shown by a delayed onset of melatonin secretion in relation to sleep time, and they proposed that circadian asynchrony may explain the strong association they found between low amplitude and low scores on many tests of cognitive functions.…”
supporting
confidence: 89%
“…Increased comorbidity in our low-RA group is consistent with reduced amplitude of the circadian rest-activity cycle reported in other disease conditions, such as hypertension, 4 cancer, 1 and mood disorders, 46 all conditions taken into account by the COTE index. In their study of schizophrenia patients, Bromundt et al 19 found that low amplitude could be associated with disturbances of circadian rhythms, as shown by a delayed onset of melatonin secretion in relation to sleep time, and they proposed that circadian asynchrony may explain the strong association they found between low amplitude and low scores on many tests of cognitive functions.…”
supporting
confidence: 89%
“…Three studies [32,36,38] included controls; one with a properly matched control group [32]; one study used a historic control group [36]; and one study measured out-and inpatients; however, these were not measured during the same time period. Generally the oncological treatment studies were of low quality and of varying design (repeated-measure or cross sectional) (Table 3).…”
Section: Study Quality and Actigraphy Methodologymentioning
confidence: 99%
“…Data processing is an important part of getting correct sleep data, and only nine studies [27e30, 34,42,44,45,48] described some kind of data processing albeit heterogeneous in each study. Only two studies [28,38] mentioned which collection mode was chosen and all used zero crossing mode (ZCM). Likewise, few studies [28,51] described which algorithm was used for the sleep analysis, and in these cases it was the ColeeKripke algorithm.…”
Section: Study Quality and Actigraphy Methodologymentioning
confidence: 99%
See 2 more Smart Citations